(untitled) (Bangladesh Journal of Medical Science, 2023)
Toxoplasma infectionduring pregnancy is an important condition to be recognized as it can result in significant morbidity to the fetus. This case described a 23-year-old lady in her first pregnancy was diagnosed with toxoplasmosis when her serology test was positive for Toxoplasma gondii specific IgM and IgG antibodies. She was asymptomatic at the time of diagnosis and continuously to be asymptomatic throughout her pregnancy. The pregnancy was uneventful with no abnormalities detected in the fetus. The laboratory diagnosis of toxoplasmosis and its application in pregnancy will be further discussed. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 222-224